Thermodynamics of Cr(VI) Adsorption on Magnetic Core-Shell Nanoparticles - Alex Fabiano Cortez Campos; Fabiana Narciso da Silva; Marcelo Rubens Braga de Almeida; Luana Cristina Alves Sales; Paulo Henrique Michels-Brito; Helena Augusta Lisboa de Oliveira (Orbital: The Electronic Journal of Chemistry, 2019)
This work focuses on the influence of temperature on Cr(VI) adsorption by nanoadsorbents based on core-shell bimagnetic CoFe2O4@g-Fe2O3 nanoparticles. The nanoadsorbents were synthesized using the hydrothermal coprecipitation method in alkaline medium followed by a surface treatment with Fe(NO3)3. The effect of initial chromium concentration and temperature of adsorption were evaluated from batch studies using 0.7 g/L of the nanoadsorbents. The results were analyzed in the framework of the Langmuir and Freundlich models and showed that the nanoadsorbents removed more than 95% of Cr(VI) in pH = 2.5 for a contact time of 30 min. The thermodynamics of the adsorption process was investigated by means of calculation of the Gibbs free energy, enthalpy and entropy changes. The results revealed that the Cr(VI) adsorption process is spontaneous, endothermic and presents an increase in randomness at the solid-solution interface.